PENINGKATAN KINERJA GURU DALAM PENGELOLAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK PEMBIMBINGAN INDIVIDUAL DI GUGUS MAJU SUNAN PRAWOTO SUKOLILO PATI - Musriyah Musriyah (Tunas Nusantara, 2019)
Improving teacher performance is one of the ways that can be taken in an effort to improve the quality of learning in schools. This research aims to test the activities of academic supervision with individual guidance in improving the performance of grade v elementary school teachers in the advanced group of Sunan Prawoto Sukolilo Pati in the 2019/2020 academic year. This research was conducted using an action research design that was designed through two cycles through procedures: (1) planning (planning), (2) implementing action (action), (3) observation (observation), (4) reflection (reflection) in each cycle. The results of this study indicate an increase in teacher performance starting early before the action by 59.20% (medium category), after the first cycle action to be 72.22% (high category), and after the second cycle action increased again to 81.97% (category high). Based on the results of the action research above, it can be concluded that Academic supervision through individual guidance conducted by the School Principal to class V teachers can improve the performance of class teachers in the State Elementary School in Sunan Prawoto Cluster, Sukolilo District, Pati District in the management of learning both aspects of learning planning, learning implementation and teacher's ability in learning.